Specific Features of the Independent Financial Audit of the Transport Companies’ Financial Statements - Natchkova, Maia (Research Papers, 2021)
The independent financial audit of the transport companies’ financial statements is characterised with specific audit procedures for the purposes of determining reliable basis for expression of audit opinion by the certified public accountants – registered auditors who audit and certify the financial statements of these companies in relation to the observance of the going concern principle. Registered auditors are required to check for the timely, fair, objective, proper, true and correct presentation, in all material aspects, of the information about the property and financial position of transport companies and their performance. The aim is to present, justify and outline in the light of the good global audit practices the specific features of the accounting reporting units formed as a result of the transport companies’ specific activities, as well as the audit procedures applied during the independent financial audit of their financial statements. This publication may be used for the performance of different types of financial audit – internal audit performed by the internal auditors of the transport companies; independent financial audit performed by the certified public accountants – registered auditors, and external audit performed by the government authorities with regard to the taxation of the transport companies’ business.